451 Late-Breaking: Saccharomyces cerevisiae boulardii stimulates immunoglobulin A production in the gut of neonate dairy calves. (5th December 2019) - Villot, Clothilde; Guan, Leluo; Skidmore, Andrew; Chevaux, Eric; Steele, Michael A
Abstract: Calves are born with a naïve immune system at birth and undergo rapid changes in terms of immunity. This study focused on evaluating the effect of S. boulardii CNCMI-1079 (SCB) supplementation from birth on immunoglobulin A (IgA) production in the gut of neonate dairy calves. Holstein bull calves (n = 20) were delivered naturally and immediately removed from the dam, and housed in individual straw-bedded pens with a random assignment to a treated group (supplementation with SCB: 10 × 10 9 CFU/d in each morning meal) or a control group (no supplementation). All the calves received two first meals of a standardized colostrum at 2 h and 12 h after birth followed by two meals per day of milk replacer (7.5% of birth BW; 260 g/kg CP; 160 g/kg crude fat, at 150g/L). Calves were euthanized at 7 d of age and samples from jejunum, ileum and colon were collected. The concentration of IgA and the gene expressions of polymeric Ig receptor (pIgR) and a receptor of plasma B cells (CD79α) were compared between the two groups and among the locations. The expression of CD79α was up-regulated in the ileum compared to jejunum and colon tissues (P < 0.01), whereas pIgR down-regulated in the ileum compared to jejunum and colon (P < 0.01). The supplementation of SCB increased the IgA concentration in the ileum and colon of treated calves compared to the control calves (respectively 1.98 ± 0.09 vs 1.18 ± 0.15 mg/g DM of ileum content, and 1.45 ± 0.14 vs 0.59 ± 0.06 mg/g DM of colon content, P < 0.001). The results suggest that one of the mechanisms by which SCB exerts an immunoprotective effect in the gut is by stimulation of IgA's secretion which may play a major role in mucosal protection in neonatal calves.